The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000494439
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Ulcerative Colitis: Is There a Relationship with Disease Extent?

Abstract: Introduction: Patients with ulcerative colitis (UC) can suffer from low serum vitamin D that can result in complications such as low bone mineral density. It can also reflect underlying disease severity. Methods: One hundred and ninety-seven patients previously diagnosed with UC from 2 European centers were prospectively recruited through the out-patient clinics. Clinical features (Montreal Classification, age, gender, previous and current medications, surgery), disease activity (Simple Clinical Colitis Activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Vitamin D exerts various anti-inflammatory, antioxidant, immunomodulatory, and antifibrotic effects ( 33 ). Typically, patients with UC have low serum vitamin D levels, which are associated with complications such as low bone mineral density ( 34 37 ). The inverse association of vitamin D with IBD or UC disease has been confirmed recently, and vitamin D supplements have been shown to help relieve disease symptoms ( 33 , 36 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D exerts various anti-inflammatory, antioxidant, immunomodulatory, and antifibrotic effects ( 33 ). Typically, patients with UC have low serum vitamin D levels, which are associated with complications such as low bone mineral density ( 34 37 ). The inverse association of vitamin D with IBD or UC disease has been confirmed recently, and vitamin D supplements have been shown to help relieve disease symptoms ( 33 , 36 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“… 168 Vitamin D levels were also decreased in UC patients, and the mean vitamin D level was lowest in patients with extensive UC (E3), suggesting a close relationship between disease progression and serum vitamin D level. 169 Furthermore, during periods of clinical UC remission, serum vitamin D levels <35mg/mL could predict the risk of relapse. 170 The ability of low vitamin D status to predict poor IBD outcomes is clarified in a review by Gubatan et al 171 A retrospective study found that 27.5 ng/mL is the optimal cut-off value for vitamin D to define the active and remission phases of IBD.…”
Section: Predictive Role For Vitamin D During Ibdmentioning
confidence: 99%
“…In a study done by Zammit et al among the European population, the disease activity index increased with decreased levels of vitamin D [ 22 ]. The study had evaluated disease activity using a simple clinical colitis activity index.…”
Section: Discussionmentioning
confidence: 99%